PENGARUH GROWTH OPPORTUNITY, STRUKTUR MODAL DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR KEUANGAN DI BURSA EFEK INDONESIA TAHUN 2018-2022) - Zalukhu, Pipit Kasih Murni; Pratiwi, Adhitya Putri (Jurnal Nusa Akuntansi, 2024)
This study aims to prove and obtain empirical evidence of the Influence of Growth Opportunity, Capital Structure, and Dividend Policy on Company Value. This study also uses a sample of financial sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The data used in this study are secondary data in the form of financial reports and annual reports. The sampling method uses the Purposive Sampling method, where from 97 financial sector companies a sample of 23 companies was obtained for 5 years so that 115 sample data were obtained. The analysis used is Panel Data Regression Analysis using the Random Effect Model (CEM) Regression and the data was processed using Eviews Software version 12. The results obtained show that the Feasibility Test (f test) that Company Value is simultaneously influenced by Growth Opportunity, Capital Structure and Dividend Policy. The results obtained show that the Partial Test (t test) shows that only the Capital Structure variable has a positive and significant effect on Company Value. Meanwhile, the Growth Opportunity variables and Dividend Policy do not have a significant effect on the Company Value variable.